Performance of two alternative methods for Listeria detection throughout Serro Minas cheese ripening - Mata, Gardênia Márcia Silva Campos; Martins, Evandro; Machado, Solimar Gonçalves; Vanetti, Maria Cristina Dantas; Pinto, Maximiliano Soares; Carvalho, Antônio Fernandes de (Brazilian Journal of Microbiology, 2016)
The ability of pathogens to survive cheese ripening is a food-security concern. Therefore, this study aimed to evaluate the performance of two alternative methods of analysis of Listeria during the ripening of artisanal Minas cheese. These methods were tested and compared with the conventional method: Lateral Flow System™, in cheeses produced on laboratory scale using raw milk collected from different farms and inoculated with Listeria innocua; and VIDAS®-LMO, in cheese samples collected from different manufacturers in Serro, Minas Gerais, Brazil. These samples were also characterized in terms of lactic acid bacteria, coliforms and physical–chemical analysis. In the inoculated samples, L. innocua was detected by Lateral Flow System™ method with 33% false-negative and 68% accuracy results. L. innocua was only detected in the inoculated samples by the conventional method at 60-days of cheese ripening. L. monocytogenes was not detected by the conventional and the VIDAS®-LMO methods in cheese samples collected from different manufacturers, which impairs evaluating the performance of this alternative method. We concluded that the conventional method provided a better recovery of L. innocua throughout cheese ripening, being able to detect L. innocua at 60-day, aging period which is required by the current legislation.
Keywords: Listeria; Raw milk cheese; Alternative methods